SWOT ANALYSIS OF INDIVIDUAL COMPONENTS WITHIN THE INNOVATIVENESS ECOSYSTEM - Michalene Eva GREBSKI; Karolina CZERWIŃSKA; Andrzej PACANA (Modern Management Review, 2022)
The article contains a qualitative assessment of the effectiveness of the individual components with in the innovativeness ecosystem. The aim of the study is to identify key performance indicators in the context of assessing the effectiveness of individual elements of the innovation network. A set of key performance indicators was developed for each of the six identified components of the innovativeness ecosystem in Northeastern Pennsylvania USA. The performance indicators were assessed using a qualitative method in the form of interviews with the key personnel and clients. The article also contains recommendations for managing an innovativeness network.  The management of the innovativeness network needs to be based  on leveraging strengths to  maximize opportunities and minimize threats.